"\\frac{d^2x}{dt^2}-6\\frac{dx}{dt}+9x=0", "x(0)=2" and "\\frac{dx(0)}{dt}=0".
Let us solve the characteristic equation:
"k^2-6k+9=0"
"(k-3)^2=0"
"k_1=k_2=3"
Therefore, the general solution is of the following form:
"x(t)=e^{3t}(C_1+C_2t)"
Then "\\frac{dx}{dt}=3e^{3t}(C_1+C_2t)+C_2e^{3t}=e^{3t}(3C_1+3C_2t+C_2)"
Taking into account that "x(0)=2" and "\\frac{dx(0)}{dt}=0" we conclude that "C_1=2" and "3C_1+C_2=0". Thus "C_2=-3C_1=-6".
Consequently, the particular solution is the following:
"x(t)=e^{3t}(2-6t)"
Comments
Leave a comment